"BUY NATIONAL" CAMPAIGNS AND FOOD COUNTRY OF ORIGIN LABELING – EU LEGAL FRAMEWORK AND ITS RELEVANCE FOR SERBIA - Jovanić, Tatjana; Cogoljević, Maja; Pejović, Duško (Economics of Agriculture, 2018)
After the entry into force of the Stabilization and Association Agreement, liberalization of trade in foodstuff with the EU and CEFTA countries, followed with broadening of the network of wholesalers and supermarkets which distribute imported agricultural products and foodstuff to Serbian consumers, origin labelling and promotion of domestic products in Serbia becomes an important issue. Using predominantly a comparative law method and qualitative analysis, on the basis of a number of possible options within the framework of national country of origin labelling schemes, the paper argues that the new quality initiative "Serbian quality" should be enriched with well-designed and coordinated measures promoting Serbia as a country of origin. By providing a legal framework and criteria for qualification whether promotion tools are legitimate or have equivalent effects to quantitative restrictions on food import, the paper aims to stimulate a discussion on the national initiative.